Zyxin expression levels in non-small cell lung cancer patients - Ilić, Dejan D; Rančić, Milan; Stoimenov Jevtović, Tatjana; Petrović, Veljko; Petrović, Marina (Vojnosanitetski pregled, 2021)
Background/Aim. Non-small cell lung cancer (NSCLC) is the most common cause of cancer-related mortality worldwide. Early detection represents one of the most promising approaches to reduce lung cancer mortality. Zyxin (ZYX) is a member of the focal adhesion protein family, recently identified as a potential early diagnostic marker for NSCLC. The aim of this study was to evaluate ZYX expression levels in NSCLC patients and compare its serum expression profiles between early and advanced clinical stages, different histological subtypes and histological grades. Methods. Blood samples were obtained from 90 patients diagnosed with NSCLC in all clinical stages and 30 patients without the clinical and radiological findings and previous history of malignancy. For the quantitative determination of human ZYX concentrations in the serum we used enzyme-linked immunoadsorbent assay (ELISA). Results. ZYX exhibited higher serum levels in NSCLC patients as compared to the control samples with exceptionally significant difference (p = 0.00). The ROC curve demonstrated a high specificity with AUC = 0.912. There were no statistically significant differences in the ZYX values between two most common NSCLC types, adenocarcinoma and squamous cell carcinoma (p = 0.758). There were no statistically significant differences in the ZYX values among different clinical stages (p = 0.518). Only 3 patients had well-differentiated tumor, and no useful data may be extracted from their samples. There were no statistically significant differences in the ZYX values between patients with moderately differentiated tumor and poorly differentiated tumor (p = 0.48). Conclusion. We found that ZYX was overexpressed in NSCLC, but its expression level was not closely correlated with the tumor size and advanced tumor, node, metastasis (TNM) stage. Our results suggest that ZYX has potential to be an early diagnostic plasma-based tumor marker for NSCLC with the same importance for both adenocarcinoma and squamous cell carcinoma.